Standard of care vs reduced-dose chemoradiation after induction chemotherapy in HPV+ oropharyngeal carcinoma patients: The Quarterback trial. (August 2019) - Misiukiewicz, K.; Gupta, V.; Miles, B.A.; Bakst, R.; Genden, E.; Selkridge, I.; Surgeon, J.T.; Rainey, H.; Camille, N.; Roy, E.; Zhang, D.; Ye, F.; et al.
Highlights: Induction chemotherapy with TPF is safe and effective in HPV Oropharynx Cancer. Induction Chemotherapy may be effective for chemoradiation de-escalation. PCR testing for HPV16 and High Risk Variants in clinical trials is necessary. Testing for p16 is insufficient for selecting patients for reduced radiotherapy. Other High Risk variants are not rare and may have a worse prognosis then HPV16. Abstract: Background: Human Papillomavirus oropharyngeal carcinoma (HPVOPC) has better progression free (PFS) and overall survival (OS) than non-HPVOPC. Standard-dose chemoradiotherapy (sdCRT) results in significant acute toxicity and late morbidity. We hypothesized that after induction chemotherapy (IC), reduced dose chemoradiation (rdCRT) would result in equivalent PFS and OS compared to sdCRT plus IC in HPVOPC and would reduce toxicity. Methods: Patients with p16+, previously untreated, locally advanced HPVOPC and ≤20 pack years smoking history received 3 cycles of IC with docetaxel, cisplatin and fluorouracil (TPF). Clinical responders who were HPV positive by type-specific PCR were randomized 1:2 to sdCRT (7000 cGy) or rdCRT (5600 cGy) with weekly carboplatin. The endpoints of the study were 3 year PFS and OS. Results: 23 patients were enrolled, 22 were evaluable for TPF toxicity and 20 were randomized, 8 to sdCRT and 12 to rdCRT. Sixteen (80%) were HPV 16+ and 4 (20%) were other high risk (HR) variants. Fourteen (70%) had high risk features: T4, N2c, or N3. Median follow up was 56 months (range 42–70). Three-year PFS/OS for sdCRT and rdCRT are 87.5% vs 83.3% (log-rank test p = 0.85), respectively. All 3 failures are locoregional within 4 months of completion of CRT; 2 were in HR variants (50%). Conclusions: rdCRT after IC resulted in similar PFS/OS compared sdCRT. These data support Phase 3 clinical trials of radiation dose reduction after IC as a treatment strategy in HPVOPC. Molecular HPV with variant testing and smoking history are necessary for de-escalation trials.